The Effect of the Number of Sunspots on Atmospheric Pressure, Temperature, and Shortwave Radiation and the Rainfall Rate for the Period from 2018-2022 (The International Journal for Scientific Research, 2024)
The sun is responsible for the climate in a very dominant way, and it is the largest supplier of energy to the Earth. Sunspots are (dark features) on the surface of the Sun, and they appear and disappear regularly. Studying climate changes due to the number of these spots and the effects resulting from them in terms of climate and their effects on Life on planet Earth is considered one of the main interests of researchers in this field. This paper aims to study the relationship between changes in the number of sunspots and some climatic factors in the atmosphere through approved and highly reliable meteorological data. An analytical model was used to reach the result, and through... The results found that the average rainfall rate was in the range of 4 mm, the average pressure rates were 968 Pascals, the average temperature rates were 10 degrees Celsius, the average radiation rates ranged between 2999MHz and 2900MHz, and the sunspots were between 10 and 39 sunspots, and from this it can be said Rainfall rates are not directly related to the increase or decrease in the number of sunspots, as there is no clear effect of that. However, in the year 2019, it was found that the increase in the number of sunspots directly affects the rates of rainfall during the spring and fall seasons as an exception, and this was confirmed through models. Previously in the laboratory, while there was no relationship between pressure rates and the number of sunspots at all, a relative relationship was found between temperature rates and sunspots, which therefore has a direct impact on radiation rates.
Keywords: Sunspots; Short Waves; Atmosphere